A Lifestyles, Belief, Culture Practices and Power Negotiation of Thai Hair Beauty Entrepreneurs: Sustainable Competitive Advantage through Critical Autoethnography - Tuntiaumpaiwong, Pichaya; Siriwong, Phitak (Humanities and Social Sciences Journal of Pibulsongkram Rajabhat University, 2026)
This study is a qualitative research employing Critical Autoethnography as its methodology. The objective is to investigate the lifestyles, belief systems, cultural practices, and power negotiations of entrepreneurs within the Thai hair beauty industry that contribute to the creation of sustainable competitive advantage. Data were collected through critical autoethnographic accounts integrated with insights from key informants amount fifteen key informants who are experts in the Thai hair industry. The findings reveal the cultural dynamics and power structures within the industry that dictate the existence, professional conduct, and sustainable competitiveness of the Thai hair beauty sector. The researchers used triangulation to verify the reliability of the data, checked the completeness of the data, and interpreted. The results of the study indicate that 1) The entrepreneurs' lifestyle is an integrated way of life that fosters long-term social engagement 2) The belief system serves as a framework that instills discipline, motivation, and professional identity 3) Cultural practices provide Thai services with a unique identity, creating experiential value that is difficult to replicate and 4) Power negotiation acts as a mechanism that determines patterns of survival, continuous adaptation, and the establishment of sustainability.